Early incident and subsyndromal delirium in older patients undergoing elective surgical procedures: a randomized clinical trial of an avoid delirium protocol - Sachdev, Alisha; Moges, Yabtsega; Rubin, Micah; Sremac, Amanda C.; Arvanitakis, Zoe; McCarthy, Robert J. (Frontiers in Anesthesiology, 2023)
Background: Pharmacological avoidance guidelines for preventing delirium have been suggested; however, there are limited pragmatic studies of these strategies. Early (<24h) delirium can be observed in the postoperative care unit and is associated with an increased risk of subsequent delirium. We examined the effectiveness of an avoid delirium protocol (ADP) in older (>65y) patients undergoing elective surgeries. Methods: The randomized controlled trial assessed an ADP developed using the American Geriatric Society’s Clinical Practice Guidelines for Postoperative Delirium in Older Adults, on early (<24h) incident or subsyndromal delirium. Delirium was assessed using the Confusion Assessment Method before surgery, in the post-anesthesia care unit and on postoperative day one. The primary outcome of early delirium was the combined incidence of incident or subsyndromal delirium. Results: Early delirium was identified in 24/235 patients (10.2%) with a risk ratio of 1.27 (95% CI 0.59 to 2.73, P=0.667) for patients randomized to the ADP. In cases with protocol adherence and no benzodiazepine use, early delirium was present in 10/73 (13.7%) compared to 14/148 (9.5%) in non-adherent cases, risk ratio 1.45 (95% CI 0.57 to 3.10, P=0.362). Lower American Society of Anesthesiologists physical class, odds ratio 3.31 (95% CI 1.35 to 8.92, P=0.008) and an inpatient admission, odds ratio 2.67 (95% CI 1.55 to 4.87, P=0.0002) were associated with early delirium. Conclusions: Our findings suggest that pharmacological avoidance protocols limiting or avoiding the use of specific classes of medications are not effective in reducing early incident or subsyndromal delirium in older patients undergoing elective surgery.